CO-EXPRESSION OF MEMBRANE-BOUND TUMOR NECROSIS FACTOR-α RECEPTORS IN MAJOR SUBPOPULATIONS OF IMMUNOCOMPETENT CELLS IN HEALTHY INDIVIDUALS AND PATIENTS WITH RHEUMATOID ARTHRITIS AS WELL AS BRONCHIAL ASTHMA - Yu. V. Zhukova; A. A. Alshevskaya; F. D. Kireev; O. A. Chumasova; N. S. Shkaruba; A. E. Sizikov; Yu. A. Lopatnikova; D. V. Demina; A. V. Karaulov; A. N. Silkov; S. V. Sennikov (Медицинская иммунология, 2021)
A pleiotropic cytokine TNFα is an important inflammatory mediator of a number of diseases; its biological functions are fulfilled through two different receptors, TNFR1 and TNFR2. Changes in the ratio between these types of receptors shifting the balance between the pro-apoptotic and proliferation signaling pathways play a crucial role in eliciting the cell response to TNFα. The pathological processes in the body can alter the levels of TNFR1 and TNFR2 expression on the cells involved in disease development. Therefore, this study was aimed at investigating the level of co-expression of type 1 and 2 TNFα receptors in the major subpopulations of peripheral blood cells in patients with rheumatoid arthritis (RA) and bronchial asthma (BA). The greatest changes in the percentage of cells expressing TNFR1 and TNFR2 were revealed for the B-lymphocyte subpopulation. For the T-lymphocyte subpopulation, there were some differences in the percentage of cells expressing exclusively TNFR1 in RA and BA patients compared with those in healthy subjects, as well as between the RA and BA groups. A higher percentage of double-negative monocytes was observed in patients with BA and RA compared to healthy subjects. These findings indicate that the coexpression profile of TNFR1 and TNFR2 receptors in patients with RA and BA differ within these groups as well as compared to that in healthy subjects. These immune cell populations are actively involved in the pathogenesis of both rheumatoid arthritis and bronchial asthma, so the results may indicate that these cells might show different responses to TNFα as the percentage and the number of receptors on their surface vary.